Smoking and involvement of right coronary artery in ischemic heart disease - Abhinav Rastogi; Tejinder Talwar; Pankaj Shah; Nitin Gupta; Vishal V. Singh; Sajaad Manzoor (Al Ameen Medical College, 2020)
Introduction: Smoking is an independent risk factor for ischemic heart disease and acute myocardial infarction. Smoking raise both heart rate and blood pressure, thus increasing myocardial oxygen demand, moreover it also decreases the dimension of coronary vessel and coronary blood flow. Inferior wall Myocardial Infarction is consequence of disease in usually Right coronary artery, whereas anterior wall Myocardial Infarction is usually disease in left coronary artery. The aim of the study is to evaluate whether smoking influence the incidence of inferior wall MI (Right coronary artery). Objective: To find out whether there is an association between smoking and inferior wall Myocardial Infarction and an early association of atherosclerosis and ischemic heart disease with smoking. Methods: 126 patients of STElevation Myocardial Infarction admitted from the outdoor patient department/ emergency department/ Cardiology OPD in MMIMSR, Mullana, Ambala, considered for study. Those who are willing to participate and fulfilling the inclusion and exclusion criteria. Result: In our study there was a high proportion of smoker in patient with inferior wall MI than other location of MI. Smokers were prone to get myocardial infarction at a younger age as compared to others. Mortality was higher in anterior wall MI as compared to Inferior wall MI. Anterior wall MI presented with more complications i.e. cardiogenic shock and arrhythmias. Conclusion: Smoking enhance the risk of inferior wall MI more than other MI. Smoking thus appear to adversely affect the Right coronary artery to greater extent than left coronary arterial circulation by mechanism yet to be explored. Smoking leads to ischemic heart disease at early age.